Lesion Size Is Exacerbated in Hypoxic Rats Whereas Hypoxia-Inducible Factor-1 Alpha and Vascular Endothelial Growth Factor Increase in Injured Normoxic Rats: A Prospective Cohort Study of Secondary Hypoxia in Focal Traumatic Brain Injury - Thelin, Eric Peter; Frostell, Arvid; Mulder, Jan; Mitsios, Nicholas; Damberg, Peter; Aski, Sahar Nikkhou; Risling, Mårten; Svensson, Mikael; Morganti-Kossmann, Maria Cristina; Bellander, Bo-Michael (Frontiers in Neurology, 2016)
Background: Hypoxia following traumatic brain injury (TBI) is a severe insult shown to exacerbate the pathophysiology, resulting in worse outcome. The aim of this study was to investigate the effects of a hypoxic insult in a focal TBI model by monitoring brain edema, lesion volume, serum biomarker levels, immune cell infiltration, as well as the expression of hypoxia-inducible factor 1-alpha (HIF-1α and vascular endothelial growth factor (VEGF). Material and methods: Female Sprague-Dawley rats (n=73, including sham and naïve) were used. The rats were intubated and mechanically ventilated. A controlled cortical impact device created a 3 millimeter deep lesion in the right parietal hemisphere. Post injury, rats inhaled either normoxic (22% O2) or hypoxic (11% O2) mixtures for 30 minutes. The rats were sacrificed at 1, 3, 7, 14 and 28 days post-injury. Serum was collected for S100B measurements using ELISA. Ex-vivo magnetic resonance imaging (MRI) was performed to determine lesion size and edema volume. Immunofluorescence was employed to analyze neuronal death, changes in cerebral macrophage- and neutrophil infiltration, microglia proliferation, apoptosis, complement activation (C5b9), IgG extravasation, HIF-1α and VEGF. Results: The hypoxic group had significantly increased blood levels of lactate and decreased pO2 (p<0.0001, respectively). On MRI post-traumatic hypoxia resulted in larger lesion areas (p=0.0173) and NeuN staining revealed greater neuronal loss (p=0.0253). HIF-1α and VEGF expression was significantly increased in normoxic but not in hypoxic animals (p<0.05, respectively). A trend was seen for serum levels of S100B to be higher in the hypoxic group at 1 day after trauma (p=0.0868). No differences were observed between the groups in cytotoxic and vascular edema, IgG extravasation, neutrophils and macrophage aggregation, microglia proliferation or C5b9 expression. Conclusion: Hypoxia following focal TBI exacerbated the lesion size and neuronal loss. Moreover, there was a tendency to higher levels of S100B in the hypoxic group early after injury, indicating a potential validity as a biomarker of injury severity. In the normoxic group, the expression of HIF-1α and VEGF was found elevated, possibly indicative of neuro-protective responses occurring in this less severely injured group. Further studies are warranted to better define the pathophysiology of post-TBI hypoxia.